Quality of life: an overview / Zuraidah Mohamed Isa ... [et al.] - Mohamed Isa, Zuraidah; Ali, Norhidayah; Andin Salamat, Azni Syafena (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The attention on the issue of the quality of life had started in the 1900s. This continued in the 1960s and 1970s which saw the increasing attention towards issues on quality of life, particularly in countries like the United States and Sweden. This indicates that the world's interests on the quality of life have been continuously renewed since the 1900s. Historically, the term quality of life is used in diverse disciplinary settings, such as in medical research, life satisfaction, economy and psychology. In psychology, the first study on quality of life was conducted in 1949, and then in 1960, studies from the mental health field began to appear. Medical research related to the quality of life started in the late 1980s and it began to gain attention in the field of economy in the 1990s. Subsequently, quality of life has become a topic of interest in social sciences in the late 20th century. In fact, the growth of quality of life is simultaneous in almost all the social sciences. In this light, Ruta, Camfield, and Donaldson (2010) study mentioned that starting from the middle of the twentieth century, issues related to the quality of life have captured many researchers' interest from different areas, such as economics, health service, social policy, medicine and psychology. Similarly, as reported by Cummins, Mccabe, Romeo, and Gullone (1994), studies on the quality of life have been done in many different areas such as economics, sociology, political science, medical sciences, philosophy and psychology.